Intracranial Pressure following Penetrating Ballistic-Like Brain Injury in Rats - Wei, Guo; Lu, Xi-Chun M.; Yang, Xiaofang; Tortella, Frank C. (Journal of neurotrauma, 2010)
Penetrating ballistic brain injury involves a leading shockwave producing a temporary cavity causing substantial secondary injury. In response to the prevalence of this type of brain trauma in the military, a rat model of penetrating ballistic-like brain injury (PBBI) was established. This study focuses on cerebral physiological responses resulting from a PBBI, specifically the immediate and delayed changes in intracranial pressure (ICP) and cerebral perfusion pressure (CPP). ICP/CPP was measured continuously in rats subjected to PBBI, probe insertion alone, or sham injury. Immediately following the PBBI, a transient (<0.1 sec) and dramatic elevation of ICP reaching 280.0 ± 86.0 mm Hg occurred, accompanied by a profound decrease in CPP to -180.2 ± 90.1 mm Hg. This emergent ICP/CPP response resolved spontaneously within seconds, but was followed by a slowly-developing and sustained secondary phase, which peaked at 24 h post-injury, reaching 37.2 ± 10.4 mm Hg, and remained elevated until 72 h post-injury. The measured decrease in CPP reached 85.3 ± 17.2 mm Hg at 3 h post-injury. By comparison, probe insertion alone did not produce the immediate ICP crisis (28.6 ± 9.1 mm Hg), and only a mild and sustained increase in ICP (13.5 ± 2.1 mm Hg) was observed in the following 3 h post-injury. Injury severity, as measured by lesion volume, brain swelling, and neurological deficits at 1, 3, and 7 days post-injury, also reflected the distinctive differences between the dynamics of the PBBI versus controls. These results not only reinforced the severe nature of this model in mimicking the ballistic effect of PBBI, but also established cerebral pathophysiological targets for neuroprotective therapies.